A Study on the Performance of Gel-Based Polyurethane Prepolymer/Ceramic Fiber Composite-Modified Asphalt - Tengteng Guo; Xu Guo; Yuanzhao Chen; Chenze Fang; Jingyu Yang; Zhenxia Li; Jiajie Feng; Hao Huang; Zhi Li; Haijun Chen; Jiachen Wang (Gels)
In order to solve various problems in traditional roads and extend their service life, new road materials have become a research hotspot. Polyurethane prepolymers (PUPs) and ceramic fibers (CFs), as materials with unique properties, were chosen due to their synergistic effect: PUPs provide elasticity and gel-like behavior, while CFs contribute to structural stability and high-temperature resistance, making them ideal for enhancing asphalt performance. PUPs, a thermoplastic and elastic polyurethane gel material, not only enhance the flexibility and adhesion properties of asphalt but also significantly improve the structural stability of composite materials when synergistically combined with CF. Using response surface methodology, an optimized preparation scheme for PUP/CF composite-modified asphalt was investigated. Through aging tests, dynamic shear rate (DSR) testing, bending rate (BBR) testing, microstructure scanning (MSCR), scanning electron microscopy (SEM), atomic force microscopy (AFM), and infrared spectroscopy (IR), the aging performance, rheological properties, permanent deformation resistance, microstructure, and modification mechanism of PUP/CF composite-modified asphalt were investigated. The results indicate that the optimal preparation scheme is a PUP content of 7.4%, a CF content of 2.1%, and a shear time of 40 min. The addition of the PUP and CF significantly enhances the asphalt’s aging resistance, and compared with single-CF-modified asphalt and base asphalt, the PUP/CF composite-modified asphalt exhibits superior high- and low-temperature rheological properties, demonstrating stronger strain recovery capability. The PUP forms a gel network structure in the material, effectively filling the gaps between CF and asphalt, enhancing interfacial bonding strength, and making the overall performance more stable. AFM microscopic morphology shows that PUP/CF composite-modified asphalt has more “honeycomb structures” than matrix asphalt and CF-modified asphalt, forming more structural asphalt and enhancing overall structural stability. This study indicates that the synergistic effect of PUP gel and CF significantly improves the macro and micro properties of asphalt. The PUP forms a three-dimensional elastic gel network in asphalt, improving adhesion and deformation resistance. Using response surface methodology, the optimal formulation (7.4% PUP, 2.1% CF) improves penetration (↓41.5%), softening point (↑6.7 °C), and ductility (↑9%), demonstrating the relevance of gel-based composites for asphalt modification.